Dampak Kualitas Data Terhadap Pengambilan Keputusan Bisnis - Ginting, Nabilah Azzahra Amin Br; Nasution, Muhammad Irwan Padli (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Business decision-making heavily relies on the quality of information used as the basis for consideration. Reliable information originates from high-quality data. This study aims to descriptively examine the impact of data quality on business decision-making using a qualitative approach through literature review. The findings reveal that aspects such as accuracy, completeness, consistency, timeliness, and data validity significantly influence the precision, efficiency, and success of decisions. Poor-quality data increases the risk of strategic errors, operational losses, and declining organizational performance. Conversely, trustworthy data strengthens analytical processes and supports more precise decision-making. Therefore, data quality should be a central concern within management systems to ensure that decision- making processes are optimal and long-term oriented.